Electronic Structure, Nonlinear Optical Properties, and Vibrational Analysis of Gemifloxacin by Density Functional Theory. Issue 3 (3rd June 2012) - Siddiqui Siddiqui, Shamoon Ahmad Shamoon Ahmad; Rasheed Rasheed, Tabish Tabish; Faisal Faisal, Mohd Mohd; Pandey Pandey, Anoop Kumar Anoop Kumar; Khan Khan, Sher Bahadar Sher Bahadar
Abstract : The non-linear optical properties of gemifloxacin (C18 H20 FN5 O4 ) have been examined using density functional theory (DFT). The molecular HOMO, LUMO composition, their respective energy gaps, MESP contours/surfaces have also been drawn to explain the activity of gemifloxacin. The equilibrium geometries and harmonic frequencies of title molecule was determined and analyzed at DFT/B3LYP level employing the 6-31G(d, p) basis set. The skeleton of both the optimized molecules is non-planar. In general, a good agreement between experimental and calculated normal modes of vibrations has been observed.